An online detection method for composite fibre tow placement accuracy. (September 2016) - Tao, Yichun; Jia, Shuhai; Duan, Yugang; Zhang, Xiaohui
Fibre composite is widely used in the field of aerospace because of its excellent performance. However, during the process of fibre placement using an automated fibre placement machine, it is difficult to guarantee accurate fibre placement. To solve the problem, this study established an online detection method for fibre tow placement accuracy. It captures the image of the detection region using an industrial charge-coupled device camera, identifies those regions with gaps in the image using computer vision methods and then acquires the gap widths which are the fibre placement accuracy of each fibre tows. When the angle between upper and lower fibre tows was small, to find the position of edges in the images accurately, we presented an improved image enhancement method based on histogram stretching. The experimental results showed that this online detection method was applicable and can quickly and effectively identify the position and width of the gaps in the detection region. Furthermore, it had high resolution, which can meet the requirements of practical engineering.